Menentukan Rujukan Rumah Sakit Terbaik Bagi Pasien BPJS Menggunakan Metode Weighted Sum Model (WSM) Pada Puskesmas - Maulida Purba; Marsono Marsono; Rina Mahyuni (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2018)
BPJS Health is one of the most important services for the community. For people who are sick and have been registered in BPJS, then the cost of treatment will be borne by the BPJS and the community is what is said as Patient BPJS. However, if a patient BPJS experiencing pain, then the patient first went to the health center or Faskes level 1 before being referred to the Hospital. Therefore, this study aims to build decision support system that has the ability to analyze in determining referral hospital for Patient BPJS at puskesmas or Faskes level 1. The method used in this research is Weighted Sum Model (WSM). The hospital samples used as many as 10 obtained from UPT Puskesmas Padang Bulan, Jln. Jamin Ginting - Medan. Based on calculations performed obtained the highest value of 77.5, ie on RS3. Therefore, this hospital is the foremost hospital as a reference for Patients BPJS. This research is expected to help the Puskesmas or Faskes level I in the city of Medan in providing hospital referrals for patients BPJS.